Arabidopsis thaliana ubiquitin-associated protein 2 (AtUAP2) functions as an E4 ubiquitin factor and negatively modulates dehydration stress response - Cho-Rong Park; Ji-Hee Min; Ying Gong; Hyunkyu Sang; Kyeong-Hwan Lee; Cheol Soo Kim (Plant Molecular Biology, 2024)

Increased Cysteine Accumulation is Essential for Salt Stress Tolerance in Arabidopsis Halotolerance 2-Like (AHL)-Overexpressing Transgenic Plants - Tinh Van Nguyen; Jeong-In Kim; Cho-Rong Park; Moon-Soo Chung; Cheol Soo Kim (Journal of Plant Biology, 2021)

Simultaneous selective removal of cesium and cobalt from water using calcium alginate-zinc ferrocyanide-Cyanex 272 composite beads - Hyun-Kyu Lee; Jung-Weon Choi; Jin-Hee Kim; Cho-Rong Kim; Sang-June Choi (Environmental Science and Pollution Research, 2021)

CU06-1004 (endothelial dysfunction blocker) ameliorates astrocyte end-feet swelling by stabilizing endothelial cell junctions in cerebral ischemia/reperfusion injury - Dong Young Kim; Haiying Zhang; Songyi Park; Yeaji Kim; Cho-Rong Bae; Young-Myeong Kim; Young-Guen Kwon (Journal of Molecular Medicine, 2020)
Cerebral ischemia, or stroke, is widespread leading cause of death and disability. Surgical and pharmacological interventions that recover blood flow are the most effective treatment strategies for stroke patients. However, restoring the blood supply is accompanied by severe reperfusion injury, with edema and astrocyte end-feet disruption. Here, we report that the oral administration of CU06-1004 (previously Sac-1004), immediately after onset of ischemia/reperfusion (I/R), ameliorated cerebral damage. CU06-1004 stabilized blood‑brain barrier by inhibiting the disruption of the tight junction-related protein zona occludens-1 and the cortical actin ring in endothelial cells (ECs) after I/R. Interestingly, CU06-1004 significantly suppressed astrocyte end-feet swelling following I/R, by reducing aquaporin 4 and connexin 43 levels, which mediates swelling. Furthermore, the degradation of β1-integrin and β-dystroglycan, which anchors to the cortical actin ring in ECs, was inhibited by CU06-1004 administration after I/R. Consistently, CU06-1004 administration following I/R also suppressed the loss of laminin and collagen type IV, which bind to the cortical actin ring anchoring proteins. Unlike the protective effects of CU06-1004 in ECs, astrocyte viability and proliferation were not directly affected. Taken together, our observations suggest that CU06-1004 inhibits I/R-induced cerebral edema and astrocyte end-feet swelling by maintaining EC junction stability. Key messages • CU06-1004 ameliorates I/R-induced cerebral injury. • EC junction integrity was stabilized by CU06-1004 treatment after I/R. • CU06-1004 reduces astrocyte end-feet swelling following I/R. • EC junction stability affects astrocyte end-feet structure maintenance after I/R.

Practical considerations for the segmented-flow analysis of nitrate and ammonium in seawater and the avoidance of matrix effects - Tae Keun Rho; Stephen Coverly; Eun-Soo Kim; Dong-Jin Kang; Sung-Hyun Kahng; Tae-Hee Na; Sung-Rok Cho; Jung-Moo Lee; Cho-Rong Moon (Ocean Science Journal, 2015)

Sulfuretin induces osteoblast differentiation through activation of TGF-β signaling - No-Joon Song; So-Mi Kwon; Suji Kim; Hyang-Jin Yoon; Cho-Rong Seo; Byunghyun Jang; Seo-Hyuk Chang; Jin-Mo Ku; Jeong-Soo Lee; Ki-Moon Park; Joung-Woo Hong; Geun Hyung Kim; et al. (Molecular and Cellular Biochemistry, 2015)

Compositions of fatty acids and phytosterols of plant-based oils and their associations with anti-oxidative capacity: Application of principal component analysis - Jae Kyeom Kim; Ho-Jeong Lim; Dong-Hoon Shin; Cho Rong Kim; Mi-Jeong Kim; Jiyeon Chun; Eui-Cheol Shin (Horticulture, Environment, and Biotechnology, 2015)

Prometaphase arrest-dependent phosphorylation of Bcl-2 and Bim reduces the association of Bcl-2 with Bak or Bim, provoking Bak activation and mitochondrial apoptosis in nocodazole-treated Jurkat T cells - Cho Rong Han; Do Youn Jun; Ji Young Lee; Young Ho Kim (Apoptosis, 2014)